LITERATION SKILL TO IMPROVE HIGHER-ORDER THINKING SKILLS IN ELEMENTARY SCHOOL STUDENTS - Mubarok, Husni; Anggraini, Dian Mustika (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2020)
Higher-order thinking skill is closely related to literacy skills. However, data from PIRLS 2011 states that the reading ability of elementary school students in Indonesia is relatively low because it is ranked 42 out of 45 countries. Data from PISA 2018, Indonesia ranked 74 out of 76 countries. Though literacy skill influences mindset. The purpose of this study is to explain: a) the basic concepts of literacy, b) the basic concepts of High Order Thinking Skills, and c) the literacy skill to improve high order thinking skills in elementary school students. The approach used in this study is qualitative. The research method used is content analysis. The data sources are journals and books related to literacy and high order thinking skills. The results of this study are: first, literacy is the ability to interpret information critically and can convey knowledge to others accurately. Second, higher-order thinking skills is the process of thinking students at a higher level of knowledge from various cognitive concepts such as analysis, synthesis, evaluation, and creation. Third, literacy skills improve higher-order thinking. The strategies used by schools include conditioning literacy-friendly physical environments, seeking social and affective situations as literate models of communication and interaction, and striving schools as a literate academic environments.